In & Out of the Classroom: Reflections on Identity, Technology, and the Radio Project - Marsh, Charity (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2006)
In this article I share my reflections on the radio project, a pedagogical tool that I incorporated in my upper-level seminars while teaching at University of Regina from 2004 to 2006. My analysis interrogates the merits (and disappointments) of the radio project as a productive (and potentially transgressive) pedagogical tool. I draw on theorists Spivak and Britzman in order to think about how social bonds are mediated by a technological environment outside the conventional university classroom. Furthermore, I explore how, through alternative pedagogies such as the radio project, social bonds may develop through processes of identification rather than identity politics.